Multi-diagnostic analysis of plasma filaments in the island divertor. (20th November 2019) - Zoletnik, S; Anda, G; Biedermann, C; Carralero, A D; Cseh, G; Dunai, D; Killer, C; Kocsis, G; Krämer-Flecken, A; Otte, M; Shanahan, B; Szepesi, T; et al.
Abstract: Filaments or blobs are well known structures in turbulence in magnetic fusion devices, they are considered to be the major cross-transport channel in the scrape off layer. They originate at the last closed magnetic flux surface and propagate out on the low field side of toroidal devices due to polarization in the curved magnetic field. The Wendelstein 7-X stellarator has a complex three-dimensional magnetic field structure and additionally the plasma is bounded by a chain of magnetic islands, forming an island divertor. After the first observation of filaments in Wendelstein 7-X with video cameras a multi-diagnostic study is presented in this paper to reveal their 3D structure and dynamics. Filaments are seen to be born at the edge and, at least in some cases, seen to extend to up to 4 toroidal turns. After moving radially out a few cm they enter the edge island. Here they disappear from the equatorial plane and about 200 microseconds later reappear on the outboard side of the island. A long-wavelength (∼20–30 cm) quasi coherent mode is observed in both regions where filaments appear. The similarities and differences between the filaments seen in W7-X and other devices are discussed. Possible explanations for this strange radial propagation are considered, together with the likely role of filaments in the edge and island density profile.